The Effort of Community Police Officer’s in Preventing Burglaries in the Jurisdiction of Grobogan Police Resort - Yosep Pasaribu (Indonesian Journal of Police Studies, 2022)
The high unemployment rate is thought to be one of the causes of the increase in crime rates. One of the criminal acts that are of concern to the legal apparatus is the crime of burglary. The National Police is responsible for conducting community development in accordance with Law No. 2 of 2002 concerning the Indonesian National Police. This coaching task is carried out by who acts as the community police officer pearhead of the National Police in carrying out pre-emptive and preventive actions. There are two problem formulations that become the main issue, namely how the operational guidance of counseling by community police officer and how the efforts of the officer unit in preventing the criminal act of burglary. Furthermore, the author uses management theory, communication theory, and crime prevention theory as an analytical knife. While the method used in this research is descriptive analysis with the focus of research on the efforts of the community police officer through counseling guidance in preventing fraudulent crimes in the jurisdiction of the Grobogan police resort. From the results of the study, it was found that the implementation of counseling guidance by the community police officer of Grobogan police resort was not optimally carried out so that it had an impact on increasing the number of thefts by weighting. Therefore, it is necessary to take troubleshooting steps so that it can reduce the theft rate by weighting. The efforts of the community police officer unit in implementing counseling guidance have not been optimally implemented. Therefore, it is recommended to improve the performance of the Binmas unit by making technological innovations/breakthroughs such as the use of technology through the Binmas Online System (BOS V-2) application.